(untitled) - Pei, Mario (New York, 1949)
From the dawn of time to the mid-twentieth century...Mario Pei discusses the formation and development of language - the weapon by which mankind has advanced from savagery to civilization. New features in this revised edition: -A new chapter on "SELF-DESIGNATION" discusses the names by which countries and people call themselves, as opposed to the names outsiders give them. -A new chapter on "LANGUAGE AND PSYCHOLOGY" covers one of the mysterious areas of language - the connection of words with the mental processes of both the individual and the social group. -Detailed discussion of such additional languages as Vietnamese and the African tongues.
Keywords: Ngôn ngữ và ngôn ngữ,Language and languages